Sustainable tourism: a new paradigm shift in India’s travel and tourism industry - Dhama, Neeru; Anil, Kanwal (Anais Brasileiros de Estudos Turísticos, 2024)
Many tourist destinations in emerging countries, such as India, Nepal, and Sri Lanka, have witnessed significant effects of the pandemic on their business, thereby adversely hitting the sector and their related economies. This research focuses on the emergence and remediation of the numerous post-pandemic problems witnessed by the Indian tourism sector and explores potential technological solutions to these grueling issues. Additionally, to attain the goal of sustainable tourism, this study analyses the initiatives launched by the Government as part of India’s Digital Tourism Mission to support and revive the Indian tourism industry. Primary and secondary data were utilized in the study to identify the importance of digital transformation in the tourism sector. This research demonstrates the post-pandemic concerns of the sustainable tourism industry and highlights the resilient approaches the sample takes to the industry for emerging issues with the help of Quadruple’s bottom line. It also culminates in how they use digital technology to tackle the industry’s obstacles and the nation’s economy. Additionally, it will highlight the various steps the Indian Government has taken to introduce digital technology to support the travel and tourism sector with specific reference to the National Digital Tourism Mission (NDTM) and put in place a paradigm shift in favor of digital tourism to realize the objective of sustainable and responsible travel.